60=-16t2-64t

Simple and best practice solution for 60=-16t2-64t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=-16t2-64t equation:



60=-16t^2-64t
We move all terms to the left:
60-(-16t^2-64t)=0
We get rid of parentheses
16t^2+64t+60=0
a = 16; b = 64; c = +60;
Δ = b2-4ac
Δ = 642-4·16·60
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(64)-16}{2*16}=\frac{-80}{32} =-2+1/2 $
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(64)+16}{2*16}=\frac{-48}{32} =-1+1/2 $

See similar equations:

| x²–7x=-10 | | -1/2y+2/3=1/2 | | 0.5x+4=0.67+1 | | 4x+8=(-5x)+5 | | x/10=5x= | | 4x+8=-5x+5 | | 2u=1=9 | | x/12+1=2 | | 10y+3=10y+3 | | 119=y-14 | | 10y+3=10y+5 | | x/7-2/14=(6+5x)/7+(6+2x)/1 | | 10y=14y | | 2(2y+8)+y=71 | | 3x-12=-1x+28 | | 2y+y=71 | | -16v=0 | | (49/81)^x=1 | | -2=n/3+4 | | (t+2)^2+(t-1)^2=9 | | 30-l=44 | | s-35=19 | | 18x-14=8+4-4 | | 3x-32+2x+26=180 | | 2(m+4)=-12 | | 7x+1/2=2(3x+1) | | z+23=6 | | 0=-2(6+x-16 | | 6/x+1=2 | | 12=7x+4(3-x | | 4y+13=22 | | 4x+3(2-x)=12 |

Equations solver categories